Electrohydraulic Servo Shaker Control Based on the Single Layer Flexible Structure Load - Tao Wang; Jinchun Song (Shock and Vibration)
As a kind of equipment commonly applied in laboratory vibration test simulation, the shaker has been widely used in many important fields of scientific research on experimental engineering vibration. It is employed for the numerical simulation of seismic activities of large buildings to quickly and quantitatively detect and calculate building components related to different building forces, analyze and study various changes of on-site structural forms and the influence mechanism of common earthquake damages or deformations with the actual existence of large-scale seismic activities, as well as to test the antiseismic strengthening structure of buildings to reduce the impact of destructive earthquakes on buildings losses. In general, the load of the shaker is regarded as a rigid structure. But in terms of the load of an electrohydraulic servo shaker with a flexible structure, the system control tends to be nonlinear accompanied by the output signals distorted. In order to achieve the goal of improving the waveform accuracy of shaking tables, it is necessary to combine the corresponding control algorithm strategy. Hence, in compliance with the working principles and functions of shaking table systems, the reasons for the coupling between flexible structure loads and shaking tables are carefully analyzed in this paper. Meanwhile, a control strategy based on the Luenberger observer control method is proposed to effectively realize the coupling suppression within the system and make the output signals of the shaking table reach the required accuracy. Finally, by comparing the frequency characteristic curves of the system before and after the introduction of the Luenberger observer, as well as the output and input analog signals, it can be seen that the Luenberger observer can effectively suppress the impact of oscillations within the system and reproduce the accuracy of the input signals.